Ablation of GSDMD Attenuates Neurological Deficits and Neuropathological Alterations After Traumatic Brain Injury - Du, Hao; Li, Chang-Hong; Gao, Ruo-Bing; Cen, Xiao-Qing; Li, Ping (Frontiers in Cellular Neuroscience, 2022)
Pyroptosis plays a significant role in neuroinflammation after traumatic brain injury (TBI). However, the role of pyroptosis executor Gasdermin D (GSDMD) in neurological deficits and neuropathological alterations after TBI have not been elucidated. Our results demonstrated that GSDMD-KO exerted striking neuroprotective effects on motor dysfunction and neuropathological alterations (loss of synaptic proteins, microglia activation, astrogliosis, dendrite injury, and neuron death) at 3 days after TBI. GSDMD-KO inhibited the expression and release of pro-inflammatory cytokine releases (IL-1β and TNF-α) while promoting those of anti-inflammatory cytokines (IL-10 and TGF-β1). The temporal pattern of diverse inflammasome signals showed long-lasting elevations of NLRP3, caspase 1, and caspase 1 p20 after TBI, rather than NLRP1, NLRC4 or AIM2, similar to the change in GSDMD postinjury; and NLRP3-KO not only inhibited the expression and cleavage of GSDMD but also attenuated the loss of synaptic proteins and neurological deficits. Notably, RNA sequencing showed both GSDMD-KO and NLRP3-KO reversed the global expression of neuroinflammation- and neuropathology-related genes after TBI. Our findings proved that the inhibition of GSDMD exerts neuroprotective effects after TBI and is mainly driven by the NLRP3 inflammasome. GSDMD serves as a potent therapeutic target for the treatment of TBI.